2018
DOI: 10.3892/ijmm.2018.3984
|View full text |Cite
|
Sign up to set email alerts
|

Guanine and nucleotide binding protein 3 promotes odonto/osteogenic differentiation of apical papilla stem cells via JNK and ERK signaling pathways

Abstract: Odonto/osteogenic differentiation of stem cells from the apical papilla (SCAPs) is a key process in tooth root formation and development. However, the molecular mechanisms underlying this process remain largely unknown. In the present study, it was identified that guanine and nucleotide binding protein 3 (GNAI3) was at least in part responsible for the odonto/osteogenic differentiation of SCAPs. GNAI3 was markedly induced in mouse tooth root development in vivo and in human SCAPs mineralization in vitro. Notab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Notably, GNAI3 has been identified as one of these disease-related proteins after GATA4 deletion by isobaric tags for relative and absolute quantification (iTRAQ) method [27]. Accordingly, we inferred that Gnai3 was closely related to osteogenesis processes, and our previous research on the role of Gnai3 in odontogenesis and osteogenesis in stem cells from the apical papilla preliminary supported this hypothesis [8]. In this study, both in vitro and in vivo knockdown of Gnai3 were conducted, and the obtained results were in agreement with our hypothesis.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Notably, GNAI3 has been identified as one of these disease-related proteins after GATA4 deletion by isobaric tags for relative and absolute quantification (iTRAQ) method [27]. Accordingly, we inferred that Gnai3 was closely related to osteogenesis processes, and our previous research on the role of Gnai3 in odontogenesis and osteogenesis in stem cells from the apical papilla preliminary supported this hypothesis [8]. In this study, both in vitro and in vivo knockdown of Gnai3 were conducted, and the obtained results were in agreement with our hypothesis.…”
Section: Discussionsupporting
confidence: 51%
“…Importantly, GNAI3 has been found to hold a potential correlation with cartilage degeneration in the rat model of osteoarthritis [7]. However, the mechanistic connection of GNAI3 with osteogenesis remains poorly understood [8]. The homeobox genes distal less homeobox 5 (DLX5) and distal less homeobox 6 (DLX6) play critical functions in cranial neural crest cells (NCCs) and drive the primary normal lower jaw patterning.…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian TAS2Rs are expressed in several extra-gustatory tissues, e.g., the upper airways, , lungs, gastrointestinal tract, , brain, bladder, and testis, as well as immune competent cells, such as blood monocytes and leukocytes and gingival fibroblasts. , For gingival fibroblasts, Zhou et al recently published the protein expression of guanine nucleotide-binding protein G subunit alpha 3 (GNAT3), an upstream GPCR signaling protein, and provided results that suggest an involvement of TAS2Rs in cellular downstream inflammatory responses . In the here-presented work, the HGF-1 cells studied were stained positive for GNAI3, thereby confirming the presence of another signaling subunit in addition to GNAT3 reported by Zhou et al In recent works, it has been shown that in stem cells of the apical papilla (SCAPs), GNAI3 plays an important role in mineralization and tissue regeneration via the c-Jun N-terminal kinase (JNK) and the extracellular-signal regulated kinase (ERK) signaling . For HGF cells, presenting the predominant cell type in gingival connective tissue, GNAI3 is known to promote wound healing by promoting the generation of an extracellular matrix.…”
Section: Discussionmentioning
confidence: 81%
“…GNAI3 is primarily expressed in Hertwig's epithelial root sheath (HERS) and the surrounding mesenchyme in mice. Moreover, knockdown of GNAI3 could inhibit the proliferation, migration, and odonto/osteogenic differentiation of CD90 + /CD44 + /CD45 − /CD14 − SCAPs by inactivating c-Jun N-terminal kinase (JNK) and extracellular-signal regulated kinase (ERK) signaling pathways [ 117 ].…”
Section: Key Markers Of Dental-derived Mscsmentioning
confidence: 99%